Dinamika Pemidanaan di Era Modern: Antara Keadilan Restoratif dan Retributif - Yuli W, Yuliana; Benedictus Roring, Edward; Satino; Widoretno Putri, Citraresmi; Kayowuan Lewoleba, Kayus (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Criminal law, as an important pillar in the criminal justice system, continues toexperience development and dynamics along with changing times. In this modern era,various discussions and discussions about punishment have emerged, including the debatebetween restorative and retributive justice approaches. This journal was created by havingcollaborative scientific studies with each other in order to aim to discuss in depth thedynamics of punishment in the modern era, with a focus on comparison and analysis ofthe two approaches.